2023
DOI: 10.1186/s12916-023-02750-9
|View full text |Cite
|
Sign up to set email alerts
|

In silico formulation of a next-generation multiepitope vaccine for use as a prophylactic candidate against Crimean-Congo hemorrhagic fever

Abstract: Background Crimean-Congo hemorrhagic fever (CCHF) is a widespread disease transmitted to humans and livestock animals through the bite of infected ticks or close contact with infected persons’ blood, organs, or other bodily fluids. The virus is responsible for severe viral hemorrhagic fever outbreaks, with a case fatality rate of up to 40%. Despite having the highest fatality rate of the virus, a suitable treatment option or vaccination has not been developed yet. Therefore, this study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…As antigenicity is a crucial factor in vaccine development, we initially predicted antigenicity. As antigenicity is a crucial factor in vaccine development, we initially predicted the antigenicity 52 . The ANTIGENpro ( https://scratch.proteomics.ics.uci.edu/ ) website was conducted to confirm the antigenicity of the selected protein,which is a part of Scratch protein predicter.…”
Section: Methodsmentioning
confidence: 99%
“…As antigenicity is a crucial factor in vaccine development, we initially predicted antigenicity. As antigenicity is a crucial factor in vaccine development, we initially predicted the antigenicity 52 . The ANTIGENpro ( https://scratch.proteomics.ics.uci.edu/ ) website was conducted to confirm the antigenicity of the selected protein,which is a part of Scratch protein predicter.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the immunological simulation of the vaccine candidates revealed that the vaccine has the potential to induce immune responses in people that closely resemble those seen in real-life situations. In conclusion, researchers determined that the developed multiepitope vaccine candidates will provide exceptional preventive characteristics against CCHF [ 217 ].…”
Section: Vaccination Methods Against Cchfvmentioning
confidence: 99%
“…Antibodies produced in response to this vaccine by immunized individuals have minimal neutralizing activities. [ 217 ] CCVax and MBVax vaccines Inactivated vaccines The humoral IgG responses showed that the MBVax and CCVax candidates, which were more robustly elicited in all CCVax groups than in MBVax animals, improved the IgG endpoint titers dose-dependent manner. [ 39 ] Experimental vaccines Recombinant vesicular stomatitis viruses (rVSV) vaccine The vector was well tolerated and exhibited complete efficacy when tested against a clinical strain of CCHFV.…”
Section: Vaccination Methods Against Cchfvmentioning
confidence: 99%
“…The front of the adjuvant was attached with a bifunctional linker EAAAK. Subsequently, CTL, HTL, and LBL epitopes were linked together through AAY, GPGPG, and KK linkers, respectively ( 66 ). Initially, the vaccine adjuvant was attached to the front of the vaccine using the EAAAK linker, which consists of helix-forming peptides of various lengths.…”
Section: Methodsmentioning
confidence: 99%